THE INTERSECTION OF ISLAM AND ADAT IN POLITICS: The Pakpak Muslim Community - Harahap, Mardian Idris; Utomo, Wahyu Wiji (Ulul Albab: Jurnal Studi Islam, 2024)
The Sulang Silima institution, a traditional authority within the Pakpak community, plays a critical role in shaping social norms and political structures, with its intersection with Islam revealing significant socio cultural, legal, and political implications. This research examines how Sulang Silima influences local political decision-making, particularly through its involvement in the selection of political leaders, thereby demonstrating the fusion of Islamic principles with customary traditions. Employing a descriptive qualitative method, the study investigates the dominance of Sulang Silima in determining social and political policies, with a focus on the manifestation of identity politics in the Pakpak context. Data were collected through in-depth interviews, participatory observation, and document analysis, and interpreted using thematic analysis to extract key themes and patterns. The findings reveal that Sulang Silima acts as a powerful legitimizing body, integrating Islamic moral frameworks with indigenous political customs to influence community leadership and governance. This intersection of religion and tradition has created a distinctive political culture in which customary institutions serve as gatekeepers of authority, identity, and social order. However, the embeddedness of identity politics within this intersection raises concerns about the potential for exclusion, marginalization, and, at a broader level, national disintegration. This study contributes to the growing body of literature on the interplay between religion, tradition, and politics in Indonesia, emphasizing the urgency of understanding such intersections to promote inclusive political systems. By analyzing Sulang Salima's role, the research highlights how traditional and religious institutions can both stabilize and challenge democratic processes in contemporary society.